Guidance for Children with Problematic Behavior in Elementary Schools: A Literature Review on the Effective Intervention Techniques and Models - Amrina Rosada; Dira Putri (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2025)
Guidance and counseling services in elementary schools are very important, especially related to the implementation of guidance activities for children with behavioral problems. The purpose of this article is to provide insights to various stakeholders about the implementation of guidance activities, focusing on effective techniques and intervention models in addressing problematic children. The method used to produce this article is a literature review. The results of the literature study on the implementation of guidance and counseling activities in elementary schools are as follows: 1) implementation of guidance and counseling in elementary schools, 2) education and training of guidance for children in elementary schools, 3) skills in conducting counseling activities for children, and 4) characteristics of children with behavioral problems. This document is expected to be useful in the implementation of guidance and counseling in elementary schools to address problematic children.